Effects of New Economic Reality on Social Changes: A Cross-Cultural Analysis - Galimova, Gulnaz V.; Panchenko, Olga L.; Mukhametzyanova, Flera G.; Mendibaev, Nuratbek (Journal of History Culture and Art Research, 2018)
The paper presents a cross-cultural analysis of the life quality of the rural population on the materials from various sources in Russia and Kyrgyzstan. A brief review of the research field, foreign and domestic works is presented. The problem potential of the life quality of the rural population is revealed based on the materials of our empirical research. Methods of research were a mass survey (Republic of Kyrgyzstan), analysis of statistical data for the Russian Federation and the Republic of Kyrgyzstan. The authors made a conclusion about the predominantly negative influence of modern socio-economic processes on the life quality of the rural population. The similarity of situations in both regions is ascertained and the necessity of optimizing the policy pursued with respect to rural areas is justified.